A plea for end-of-life discussions with patients suffering from Huntington's disease: the role of the physician. Issue 10 (22nd December 2012) - Booij, Suzanne J; Engberts, Dick P; Rödig, Verena; Tibben, Aad; Roos, Raymund A C
Abstract : Euthanasia and physician-assisted suicide (PAS) by request and/or based on an advance directive are legal in The Netherlands under strict conditions, thus providing options for patients with Huntington's disease (HD) and other neurodegenerative diseases to stay in control and choose their end of life. HD is an inherited progressive disease characterised by chorea and hypokinesia, psychiatric symptoms and dementia. From a qualitative study based on interviews with 15 physicians experienced in treating HD, several ethical issues emerged. Consideration of these aspects leads to a discussion about the professional role of a physician in relation to the personal autonomy of a patient. Such a discussion can raise awareness that talking about end-of-life wishes with an HD patient is part of the legal, professional and moral responsibility of the physician, and that a letter of intent on behalf of the physician can improve active participation in the process. Discussion of these issues can help to advance the debate on euthanasia and PAS in HD and other neurodegenerative diseases.